KONTEKSTUALISASI AL-QUR’AN DAN HADIS TERHADAP PEMBARUAN HUKUM ISLAM MENURUT FAZLUR RAHMAN - Nurfatihah, Amalia (Jurnal Studi Islam, 2024)
The purpose of this writing is to determine Fazlur Rahman's views or understanding of the study of the contextualization of the Al-Qur'an and Hadith towards Islamic legal reform. In this research, an in-depth analysis of the reform of Islamic law was initiated by Fazlur Rahman by contextualizing the Al-Qur'an and Hadith as basic reference sources. So, the author uses a descriptive approach to make systematic, factual and accurate research regarding data as a step in clearly defining the approach and data collection used regarding the contextualization of the Al-Qur'an and Hadith according to Fazlur Rahman's understanding, then analyzed to come to a conclusion. In data collection techniques, the author uses the Library Research method. The results of this research are a contextual interpretation of the Al-Qur'an and Hadith offered by Fazlur Rahman regarding the reform of Islamic law as a logical consequence of his views.